Prevalence and correlates of cannabis abuse among residents in the community of Fort McMurray, a city in Northern Alberta which had endured multiple natural disasters - Obuobi-Donkor, Gloria; Eboreime, Ejemai; Shalaby, Reham; Agyapong, Belinda; Agyapong, Vincent I. O. (Frontiers in Psychiatry, 2022)
Background Cannabis is one of the widely used drugs that users may abuse. Researchers have given attention to cannabis use among the general population, while vulnerable populations who have experienced multiple traumas may be at risk of cannabis abuse. Other factors may influence cannabis abuse among people exposed to traumas. Objective The study aims to determine the prevalence and correlates of cannabis abuse among Fort McMurray, Alberta, Canada, residents. Methods A cross-sectional survey was conducted using an online questionnaire. Sociodemographic data, trauma exposure, and clinical characteristics were collected to identify the possible predictors of cannabis abuse. Data were analyzed with SPSS version 25 using a bivariable test of association with the chi-square test and binary logistic regression analysis. Correlation analysis was also performed to ascertain likely cannabis abuse and the association with other mental health conditions. Results Overall, participants who completed the survey were one hundred and eighty-sixed out of the two hundred and forty-nine residents who accessed the online survey, giving a response rate of 74.7%. The prevalence of likely cannabis abuse among participants was 14%. Most of the participants were females (159, 85.5%), employed (175, 94.1%), owned their house (145, 78.0%), and 103 (60.6%) reported being exposed to at least a trauma. Participants living in rented accommodation were nearly four times more likely to abuse cannabis (OR= 3.86; 95% CI: 1.34–11.14) than those owning their houses. Similarly, male participants were more than six folds more likely to abuse cannabis than the female gender (OR= 6.25; 95% CI: 1.89 – 20), and participants in a relationship were six times more likely to abuse cannabis than participants not in a relationship (OR= 6.33; 95% CI: 1.67–24.39). The study also found significant association of depressive symptoms (X2 = 4.561; p = 0.033) and anxiety symptoms (X2 = 4.700; p = 0.030) with likely cannabis abuse. Conclusion Demographic factors significantly predicted likely cannabis abuse among residents of Fort McMurray. Cannabis abuse is correlated with anxiety and depression symptoms; therefore, it is essential to mobilize resources to support vulnerable communities and manage cannabis abuse.